Mechanical performance of an improved semi-rigid joint system under bending and axial forces for aluminum single-layer reticulated shells. (September 2019) - Ma, Huihuan; Yu, Lingwei; Fan, Feng; Yu, Zhiwei
Abstract: In this study, the traditional Temcor joint (TR-Temcor) is modified using a central hollow hexagonal prism and some front bolts. The Finite Element Analysis (FEA) model is established and verified by experiments. Then, a parametric analysis is carried out for the improved Temcor joint (IM-Temcor). To obtain the optimal parameters for the modified joint, the key factors, namely: number and location of the front bolts, bolt-hole deviation, pretension force in bolts, thickness of front plate and heat-affected zone caused by the welding work, are considered in the FEA models. The modified joint, with the optimized factors, is analyzed for different static load conditions, considering axial pressure, axial tension, pure bending, bending with axial force, and eccentric axial forces. The overall mechanical behavior of the joint, including the M-Φ curves, initial stiffness, ultimate strength and deformation capacity, as well as the failure modes are identified. The results from the improved joint are compared with corresponding values from of the traditional Temcor joints. The results show that the central hollow hexagonal prism and front bolts significantly improves the stiffness and ultimate strength of the joint, especially when the joint is subjected to pure bending, bending with shear force, axial force, bending with certain axial force and eccentric force. Highlights: An improved Temcor joint system was designed. FE model of the joint was established and verified. Optimized analysis was conducted on the improved Temcor joint. Mechanical behavior of the improved joint under different loading conditions were identified. The new joint significantly improves the stiffness and ultimate strength of the traditional joint.